The Effect of Parents Attention, Learning Discipline and Learning Motivation to Learning Outcomes of Students at the Student Financial Accounting Class - Listinawati Haditama; Yunia Wardi; Syamwil Syamwil (International Conferences on Educational, Social Sciences and Technology)
The purpose of this research is to determine the influence of Parents Attention, Learning Discipline, and Learning Motivation to learning outcomes of students at the student Financial Accounting Class XI SMK Negeri in Business and Management Department of Padang. The population in this research were 221 students of class XI accounting. The sampling technique used is proportionate random sampling so that the sample of 142 students is obtained. Research instrument used in the form of questionnaire. Data analysis in this research using Path Analysis. The results of this research indicate that parents' attention has a significant effect and contribute to the discipline of learning. Parental attentions and discipline of learning have a significant effect on learning motivation. Attention parents, learning discipline, and learning motivation have a significant effect on the results of students' financial accounting learning class XI.